Expanding the Chemical Diversity of DNA - Guo, Chun; Kong, Dehui; Lei, Yi; Hili, Ryan (Synlett, 2018)
Nucleic acid polymers can be evolved to exhibit desired properties, including molecular recognition of a molecular target and catalysis of a specific reaction. These properties can be readily evolved despite the dearth of chemical diversity available to nucleic acid polymers, especially when compared to the rich chemical complexity of proteins. Expansion of nucleic acid chemical diversity has therefore been an important thrust for improving their properties for analytical and biomedical applications. Herein, we briefly describe the current state-of-the-art for the sequence-defined incorporation of modifications throughout an evolvable nucleic acid polymer. This includes contributions from our own lab, which have expanded the chemical diversity of nucleic acid polymers closer to the level observed in proteinogenic polymers.1 Introduction2 Polymerase-Catalyzed Synthesis of Modified Nucleic Acid Polymers3 Ligase-Catalyzed Oligonucleotide Polymerization (LOOPER)4 LOOPER with Small Modifications5 LOOPER with Large Modifications6 Evolution of Aptamers Derived from LOOPER Libraries7 Outlook
Keywords: modified nucleic acids; modified aptamers; sequence-defined polymers; ligase; in vitro selection; molecular evolution